Immune regulation by intralymphatic immunotherapy with modular allergen translocation MAT vaccine. Issue 9 (12th July 2014) - Zaleska, A.; Eiwegger, T.; Soyer, Ö.; van de Veen, W.; Rhyner, C.; Soyka, M. B.; Bekpen, C.; Demiröz, D.; Treis, A.; Söllner, S.; Palomares, O.; Kwok, W. W.; et al.
Abstract Background Allergen‐specific immunotherapy (SIT) faces problems related to side effects and limited efficacy. Direct administration of allergen extracts into lymph nodes induces increased specific IgG production and T‐cell responses using significantly lower allergen doses. Methods In this study, mechanisms of immune regulation by MAT vaccines in vitro and in allergen‐SIT of cat‐allergic rhinitis patients, who received 3 inguinal intra‐lymph node injections of MAT‐Fel d 1 vaccine, were investigated in PBMC and cell cultures for specific T‐cell proliferation, Fel d 1‐tetramer‐specific responses, and multiple immune regulatory molecules. Results MAT‐Fel d 1 vaccine was efficiently internalized by antigen‐presenting cells. This was followed by precaspase 1 cleavage to caspase 1 and secretion of IL‐1β, indicating inflammasome activation. Mat‐Fel d 1 induced specific T‐cell proliferation and an IL‐10‐ and IFN‐γ‐dominated T‐cell responses with decreased Th2 cytokines at 100 times lower doses than Fel d 1. Induction of immune tolerance by MAT‐Fel d 1‐ILIT involved multiple mechanisms of immune suppression. Early Fel d 1‐specific T‐cell activation was followed by full T‐cell unresponsiveness to allergen after 1 year in the MAT‐Fel d 1 group, characterized by increased allergen‐specific T regulatory cells, decreased circulating Fel d 1 tetramer‐positive cells, increased IL‐10 and FOXP3 expression, and change in the HR2/HR1 ratio toward HR2. Conclusions This study demonstrates the induction of allergen tolerance after 3 intra‐lymph node injections of MAT‐Fel d 1 vaccine, mediated by increased cellular internalization of the allergen, activation of inflammasome, and generation of allergen‐specific peripheral T‐cell tolerance.